United in defeat: shared suffering and group bonding among football fans. Issue 2 (4th March 2023) - Newson, Martha; Buhrmester, Michael; Whitehouse, Harvey
ABSTRACT: Purpose: Evidence shows that the least successful clubs have the most committed fans – why? Here, we test the "shared-dysphoria-pathway-to-fusion" (SDPF) hypothesis that fans of the least successful clubs become irrevocably "fused" to their club and to each other, as a result of sharing self- and club-defining memories of past defeats. Design: To assess the SDPF hypothesis, we calculated the most and least successful clubs from the UK's top league, the Premier League, over a 10-year period. We then invited fans of these clubs to complete a survey ( N = 752), comprising qualitative recollections of football events, quantitative survey measures of identity fusion and psychological kinship, and a trolley dilemma measuring willingness to sacrifice one's self to save fellow supporters. Findings: Our mediation model supported the SDPF hypothesis. Fans of Crystal Palace, Hull, Norwich, Sunderland, and West Bromwich Albion were more bonded and more willing to sacrifice themselves for other fans of their club than were fans of Manchester United, Arsenal, Chelsea, Liverpool or Manchester City. Across clubs, memories of past football defeats formed an essential part of fans' self-concepts, thus fusing them to their club. Identity fusion in turn predicted a readiness to lay down one's life to save fellow fans, and this relationship was statistically mediated by psychological kinship. Practical implications: Understanding that shared suffering can lead to extreme bonding may help sports clubs and policy makers manage crowd behaviour. Clubs will benefit from tailoring brand management and fan retainment strategies to the SDPF hypothesis. In addition, these findings provide insight into the motivations of oppressed or persecuted groups, and such others fused through shared sufferings, helping us better understand and manage the psychological processes that can lead to extreme self-sacrifice. Research contributions: This is the first study to show mediational support for the SDPF hypothesis in relation to football fandom. The psychological mechanism that may have once bonded embattled foraging groups in our ancestral past, now works in the modern world to unite soccer fans, among other kinds of groups, in their millions.